INDONESIAN SENIOR HIGH SCHOOL ENGLISH TEACHERS’ VIEWS ON WORLD ENGLISHES IN L2 INSTRUCTION - Franssisca, Ruth Eliana; Subekti, Adaninggar Septi (IJIET (International Journal of Indonesian Education and Teaching), 2022)
The present study was conducted to investigate the views of six Indonesian senior high school teachers of English on the place of World Englishes (WE) in English as second language (L2) instruction. The study used semi-structured online interviews as the method of data collection. Through Thematic Analysis, it found several main findings. The teachers introduced varieties of accents to motivate their students and nurture respect towards accented English. They, however, did so at varying degrees, several in the intra-curricular activities, one in extracurricular activities only. Though they had different perspectives on the level of importance of introducing students with varieties of accents, they uniformly believed that it was acceptable for their students to speak English with local accents. The implication of the study includes accommodating WE to a certain extent in activities and assessment and raising English teachers’ awareness towards WE through accommodating it in English education majors’ curricula. Contributions, limitations, and future studies’ directions are also suggested.